PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. BPR NUSANTARA BONA PASOGIT 7 PEMATANG RAYA - Sinaga, Ria Veronica; Sembiring, Sabeth; Purba, Gresia Ruth Elsani (UNIKA Santo Thomas, 2023)
This study aims to determine and explain the influence of leadership style, financial compensation and non-financial compensation on employee performance at PT. BPR Nusantara Bona Pasogit 7 Pematang Raya. Data collection was carried out through questionnaires and documentation techniques. The research method used is quantitative, with 35 respondents taken using saturated or census sampling. Data analysis in this study used SPSS version 25. From the partial test results the t test shows tcount 2.046 > ttable 1.695 and the significance level is 0.030 <0.050 proving that leadership style has a positive and significant effect on employee performance. tcount 11.325 > ttable 1.695 and a significance level of 0.000 <0.050 proves that financial compensation has a positive and significant effect on employee performance. tcount 2.317 > ttable 1.695 and the significance level is 0.027 <0.050 proving that non-financial compensation has a positive effect on employee performance. The F test shows Fcount 68.113 > F Table 2.90 and a significant level of 0.000 <0.05 proves that leadership style, financial compensation and non-financial compensation have a positive and significant effect on employee performance. From the results of the discussion, the multiple linear regression equation obtained from the results of data processing is Y = 3.372 + 0.296X1 + 0.594X2 + 0.144X3 + e. That is, leadership style, financial compensation and non-financial compensation have a positive and significant effect on the performance of employees at PT. BPR Nusantara Bona Pasogit 7 Pematang Raya. The coefficient of determination (R Square) is 0.868, meaning that employee performance can be explained by the variables of leadership style, financial compensation and non-financial compensation of 86.8% while another 13.2% is explained by other variables not explained in this study such as work discipline, communication and enthusiasm.